Head and Face Injuries in Brazilian Victims of Homophobic Crimes - Cavalcanti, Alessandro L.; de Oliveira, Thaisy S.B.; de Oliveira, Thaliny B.S.; Cavalcanti, Christiane L.; de Oliveira, Thaiany B.S.; Cavalcanti, Alidianne F.C. (UI Scholars Hub, 2018)
Crimes against homosexuals are mostly hate crimes, and should be referred to as homophobic crimes. Objective: To investigate the occurrence of head and face injuries in victims of homophobic crimes. Methods: A retrospective study was conducted at the Specialized Police for Homophobic Crimes. Data were collected from the 56 police and medical reports corresponding to reported cases of homicide against lesbian, gay, bisexual, transsexual and transgender (LGBT, or sexual minority) in the period from May 2009 to July 2013. Variables studied related demographic profile of victims and patterns of trauma (type of arms, number of injuries and anatomical regions) were assessed. For bivariate analyses, the Chi-square and Fisher’s exact, with significance level of 5% were used. Results: 89.3% were homosexuals and 42.9 were gays. Firearms were the type of arms most used (46.4%), followed by cold steel (30.4%). Most victims presented multiple lesions (87.5%) and 44.6% presented injuries in the head and face. There was a statistically significant association between injuries in the head and face and the type of arms (P=0.001). Conclusion: Victims of homicide were mostly homosexuals and the main types of arms were firearms and cold steel. Most victims presented multiple lesions and injuries in the head and face were common and more frequent among lesbians and transvestites.